2013
DOI: 10.1093/aje/kwt305
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sleepiness, Sleep Disorders, and the Work Environment on Heavy-Vehicle Crashes in 2 Australian States

Abstract: Heavy-vehicle driving involves a challenging work environment and a high crash rate. We investigated the associations of sleepiness, sleep disorders, and work environment (including truck characteristics) with the risk of crashing between 2008 and 2011 in the Australian states of New South Wales and Western Australia. We conducted a case-control study of 530 heavy-vehicle drivers who had recently crashed and 517 heavy-vehicle drivers who had not. Drivers' crash histories, truck details, driving schedules, paym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 19 publications
1
47
0
1
Order By: Relevance
“…Interestingly however, the pooled analysis of data from the NSW and WA portions of the current study found that OSA was not associated with the risk of a crash. 11 While reasons for this difference require further investigation, it is possible that OSA has a greater impact on crash risk for WA drivers due to the vast distances they travel, isolation, monotonous scenery, and harsh climate of WA-all factors which exacerbate the effects of fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly however, the pooled analysis of data from the NSW and WA portions of the current study found that OSA was not associated with the risk of a crash. 11 While reasons for this difference require further investigation, it is possible that OSA has a greater impact on crash risk for WA drivers due to the vast distances they travel, isolation, monotonous scenery, and harsh climate of WA-all factors which exacerbate the effects of fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] However, WA has a unique road environment with vast distances between locations, extreme temperatures and weather conditions, and monotonous scenery. 12 WA is also governed by different fatigue regulations from the rest of Australia and faces specifi c challenges for heavy vehicle safety.…”
Section: S C I E N T I F I C I N V E S T I G At I O N Smentioning
confidence: 99%
“…Being a less experience driver increase the likelihood of crashing. 31 The mean workday length of this sample of drivers was 9.37 hours (SD=2.25). This was lower than the average workday length of 11.89 hours (SD=1.683) reported in a study among 600 New Zealand truck drivers.…”
Section: Discussionmentioning
confidence: 89%
“…A Turkish study by Firat and colleagues [32] suggesting that portable sleep monitoring is reliable in detecting OSA with AHI>15/h in highway bus drivers is important in this context. Given the controversies regarding the relationship between OSA severity and MVA risk in clinical cohorts versus the lack of an association between AHI and MVA risk in commercial drivers [30,33], there is also a need for development of screening tools for objective evaluation of EDS in such individuals. The Oxford Sleep Resistance (OSLER) Test [34] as well as a recently developed neurocognitive test, Gothenburg Sleep Resistant (GOSLING) Test seem to be less time-consuming and reliable tools to detect attention deficits in OSA patients with high MVA risk [35].…”
Section: Future Perspectivesmentioning
confidence: 99%